Morphological Heredity of Intermetallic Nb5Si3 Dendrites in Hypereutectic Nb-Si Based Alloys via Non-Equilibrium Solidification - Yueling Guo; Lina Jia; Wenjun Lu; Hu Zhang (Chinese Journal of Mechanical Engineering, 2022)
Abstract For hypereutectic Nb-Si based alloys, primary Nb5Si3 phases typically grow in a faceted mode during equilibrium or near-equilibrium solidification, which damages the ductility and toughness. To address this issue, here we artificially manipulate the growth morphology of Nb5Si3 using electron beam surface melting (EBSM) and subsequent annealing treatments. Results show that such a non-equilibrium solidification pathway enables the transition from faceted growth to non-faceted dendritic growth of Nb5Si3, along with evident microstructure refinement, generation of metastable β-Nb5Si3 phases and elimination of chemical segregation. The transformation from β-Nb5Si3 to α-Nb5Si3 and Nb solid solution (Nbss) particles is triggered by the annealing treatment at 1450 °C for 5 h. Also, we find the annealing-mediated formation of inherited Nb5Si3 dendrites that maintain the dendritic morphology of the original as-solidified β-Nb5Si3 dendrites. This work thus provides a feasible routine to obtain thermally stable and refined α-Nb5Si3 dendrites in hypereutectic Nb-Si based alloys.